ISSUES OF IMPROVING SPORTS TRAINING - Umarova Zulxumor Urinbayevna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The article describes the means of organizing training and increasing the level of quality of sports, and suggestions and recommendations are given after the article.